Characterization of radicals in polysorbate 80 using electron paramagnetic resonance (EPR) spectroscopy and spin trapping - Judith J. Mittag; Marie-Luise Trutschel; Helen Kruschwitz; Karsten Mäder; Julia Buske; Patrick Garidel (Elsevier, 2022)
Polysorbates are an important class of nonionic surfactants that are widely used to stabilize biopharmaceuticals. The degradation of polysorbate 20 and 80 and the related particle formation in biologics are heavily discussed in the pharmaceutical community. Although a lot of experimental effort was spent in the detailed study of potential degradation pathways, the underlying mechanisms are only sparsely understood. Besides enzymatic hydrolysis, another proposed mechanism is associated with radical-induced (auto)oxidation of polysorbates. To characterize the types and the origin of the involved radicals and their propagation in bulk material as well as in diluted polysorbate 80 solutions, we applied electron paramagnetic resonance (EPR) spectroscopy using a spin trapping approach. The prerequisite for a meaningful experiment using spin traps is an understanding of the trapping rate, which is an interplay of (i) the presence of the spin trap at the scene of action, (ii) the specific reactivity of the selected spin trap with a certain radical as well as (iii) the stability of the formed spin adducts (a slow decay rate). We discuss whether and to which extent these criteria are fulfilled regarding the identification of different radical classes that might be involved in polysorbate oxidative degradation processes. The ratio of different radicals for different scenarios was determined for various polysorbate 80 quality grades in bulk material and in aqueous solution, showing differences in the ratio of present radicals. Possible correlations between the radical content and product parameters such as the quality grade, the manufacturing date, the manufacturer, the initial peroxide content according to the certificate of analysis of polysorbate 80 are discussed.